Decision Support System: UTHM Pagoh Residential College Online Registration and Complaint - Rahmat, Hazwani; Omar, Muhammad Haiqall; Abd. Rahman, Nurul Izzahana; Saad, Nurin Afrina (Multidisciplinary Applied Research and Innovation, 2020)
UTHM students who intend to stay in Pagoh Residential College are required to come for manual registration before every semester begins. However, most of them came from hometown afar. In addition, residential college students are responsible for reporting any damage in their room, and getting involved in the residential college activities. A preliminary interview with the recsidential college administration indicates that the residential college management is currently using a manual business process in allocating room upon student registration where students are given a room without consideration of their race or religion. However, the majority of Malaysians, especially UTHM students are mostly Muslim. Therefore, providing residential with proper room allocation is crucial as there is a possibility where students cook in the college or bring outside food, which is non-halal. This study aims to help students register their rooms by considering these issues using a decision-making technique, making complaints, and obtaining information about activities from residential colleges online. We have planned to evaluate the system usability and enhance it to support mobile access.